Low-Dose Paclitaxel-Coated Balloon Angioplasty versus Uncoated Percutaneous Transluminal Balloon Angioplasty for Femoropopliteal Peripheral Artery Disease: 6-Month Results in a Tertiary Care Hospital of Central India - Rathod, Jawahar; Gour, Prajwaleet; Saha, Subinay; Jaybhay, Shivprasad; Verma, Rohit (Journal of Clinical Interventional Radiology ISVIR, 2019)
Introduction Superficial femoral and popliteal arteries are the most common locations of peripheral vascular disease (PVD). Endovascular interventional therapy including drug-coated balloon (DEB) angioplasty or percutaneous transluminal angioplasty (PTA) and stenting are important options for treatment of PVD.Aims and Objectives The main objective is to compare the efficacy of DEB over PTA with optional stenting in management of obstructive femoropopliteal lesions in terms of 6-month patency rate.Materials and Methods The clinical experimental study was carried out in a tertiary care center over duration of 2 years. All symptomatic patients having lower limb PVD in femoropopliteal segment were included. Total 37 patients were included in this study in which 16 underwent plain balloon angioplasty (with 3 patients undergoing bare metal stenting [BMS]) and 21 additional underwent DEB angioplasty. Patients with previously intervened lesions, primary lesion failure, major ischemic tissue loss, poor aortoiliac or common femoral inflow, or end-stage kidney disorders were excluded.Result At 1-month follow-up, patency rates in DEB and conventional PTA ± BMS were 85.71% and 87.5%, respectively. On 6-month follow-up, patency rates were found to be 71.4% versus 37.5%, respectively (p = 0.039; significant). In case of occluded lesions, on 6-month follow-up, patency rate in DEB group was higher than that in plain balloon group (66.7% vs. 25%). In both the cohorts, success rate, i.e., patency rates were more in short and intermediate length lesions than long segment lesions. DEB was found to be superior to plain angioplasty with optional stenting in terms of 6-month patency rate.
Keywords: peripheral vascular disease; femoropopliteal; drug-eluting balloon angioplasty